Solar and wind potential of Venezuela, hybrid power supply system scenarios for the Toas Island, Zulia State (Publicaciones en Ciencias y Tecnología, 2022)
Electricity generation in Venezuela is dominated by fossil fuels and large-scale hydroelectric plants, predominating over other energy sources. The objective of this research is to determine the solar photovoltaic and wind potential and to propose scenarios of hybrid electric energy systems for Toas Island, Zulia State. In the first part, a documentary research on this potential was carried out, then with data obtained from solar irradiation and wind speed, through Global Solar, NASA Power and the use of the Homer application, a feasible project of a micro grid applied to Toas Island, Almirante Padilla Municipality, Zulia State, was presented.  Thus demonstrating that the photovoltaic, wind, battery and interconnection scenario is the best applicable option, with a levelized cost of electricity of 0.3 $/kWh, offering greater reliability and availability, with the possibility of transmitting surpluses to the electric grid.
Keywords: Levelized cost of electricity; wind energy; photovoltaic energy; microgrid